Desain Turbin Pembangkit Listrik Energi Pasang Surut Di Wilayah Perairan Desa Bagan Siapi-api Kecamatan Rokan Hilir Riau - Syaipul Azhar; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tidal energy is renewable energy. Its working principle uses water flow to turn turbin and produce electrical energy. This energy is obtained from variations in sea level caused by effects of moon’s gravity, which is combined with rotation of the earth by capturing energy contained transferly of water mass to tides. Kaplan turbine is a tool that can convert kinetic energy from water velocity, into motion energy. Analysis of Kaplan turbine performance using Compitational Fluid Dynamycs (CFD) simulation method, is the art to replace integral or Partial Derivative Equations, that explains fluid equation in algebraic form. This equation is solved numerically, to get the number of a strems at different points. Aerodynamic simulations on Kaplan turbines are carried out to determine the aerodynamic characteristics of designed Kaplan turbines. Data from Kaplan turbine aerodynamic simulation results are sufficient to meet the actual conditions, where tidal current velocity in this study site is 0.70 m/s to 1.60 m/s with head determined in various variations, namely 5.5m to 0.5m, produce turbine rotation of 7 RPM to 190 RPM with kinetic power of 3.5 kW to 1027 kW, and electrical power of 3.3 kW to 925 kW. With comparison of current speed from simulation results of 1.14 m/s to 4.41 m/s with head variations of 5.5 m to 0.5 m, resulting turbine rotation of 15 RPM to 525 RPM, with kinetic power of 6 kW to 2833 kW, and electrical power generated from 30 kW to 925 kW.Keywords: Aero Dynamycs Simulation, CFD, Energy Generation, Kaplan Turbine Design, Tides.